Development of a Competitive strategy for a Power Plants manufacturer in the Colombian Oil sector - Herrera, Maria Catalina (My University, 2009)
The main pursue of the study is to develop a competitive strategy for a power plant manufacturer in the Colombia oil sector. The study aims to identify the main theories of competitive strategy and competitive advantage by analyzing sources of competitive advantage and the competitive environment of the firm. The strategy is understood as a combination of actions, where the right use of resources is vital, it means knowing how, when and which of those resources should be employed according to the market environment. Thus, a superior combination of resources within a specific market condition will lead to reach a better position and to create value to customer, which is the main aim of any strategy. The theoretical part was concentrated on analyzing the concept of Competitive Strategy developed by Michael Porter (1980). Along with the Industrial based approach, the Resource based view and the cooperation strategy to determine the sources of competitive advantage. Moreover, the research methodology chosen to carry out the study was a case study approach and a qualitative data analysis. The data was collected through telephone interview and open ended questionnaires sent by e-mail. Three managers from the case study company participated in the research. The study also involves the view of two buyers of power plants. The analytical part of the study was concentrated on examining characteristics and market condition of the Colombian oil sector, the competitive environment of the firm, its position and possible sources of competitive advantage of the case company. As a result of the empirical finding the research suggests that the case company should follow a focus/differentiation strategy in order to work closer with prospective and current customers with the aim of developing a competitive advantage.
Keywords: Competitive Strategy; Competitive advantage; Resource Based View.; fi=Marketing|; fi=Master's Degree Programme in International Business|